Introduction to the updated Australian and New Zealand consensus guidelines for the use of antifungal agents in the haematology/oncology setting, 2014. Issue 12 (December 2014) - Slavin, M. A.; Thursky, K. A.; Worth, L. J.; Chang, C. C.; Morrissey, C. O.; Blyth, C. C.; Chen, S. C.; Szer, J.
Abstract This article introduces the second revision of the Australian and New Zealand consensus guidelines for the use of antifungal agents in the haematology/oncology setting. The current update occurs within the context of a growing population at risk of invasive fungal disease, improved understanding of risk factors, availability of new diagnostic tests, a much‐expanded evidence base and changing clinical paradigms. Here, we provide an overview of the history and purpose of the guidelines, including changes in scope since the last clinical update was published in 2008. The process for development, and for enabling review of draft recommendations by end‐users and other relevant stakeholders, is described. The approach to assigning levels of evidence and grades of recommendation is also provided, along with a comparison to international grading systems.